Research Priorities to Support Effective Manta and Devil Ray Conservation - Stewart, Joshua D.; Jaine, Fabrice R. A.; Armstrong, Amelia J.; Armstrong, Asia O.; Bennett, Michael B.; Burgess, Katherine B.; Couturier, Lydie I. E.; Croll, Donald A.; Cronin, Melissa R.; Deakos, Mark H.; Dudgeon, Christine L.; Fernando, Daniel; et al. (Frontiers in Marine Science, 2018)
Manta and devil rays are filter-feeding elasmobranchs that are found circumglobally in tropical and subtropical waters. Although relatively understudied for most of the 20th century, public awareness and scientific research on these species has increased dramatically in recent years. Much of this attention has been in response to targeted fisheries, international trade in mobulid products, and a growing concern over the fate of exploited populations. Despite progress in mobulid research, major knowledge gaps still exist, hindering the development of effective management and conservation strategies. We assembled 30 leaders and emerging experts in the fields of mobulid biology, ecology and conservation to identify pressing knowledge gaps that must be filled to facilitate improved science-based management of these vulnerable species. We highlight focal research topics in the subject areas of taxonomy and diversity, life history, reproduction and nursery areas, population trends, bycatch and fisheries, spatial dynamics and movements, foraging and diving, pollution and contaminants, and sub-lethal impacts. Mobulid rays remain a poorly studied group, and therefore our list of important knowledge gaps is extensive. However, we hope that this identification of high priority knowledge gaps will stimulate and focus future mobulid research.